Co‐Production and Implementation of 'Count Me In': A Bottom‐Up Approach to Inclusive Research and Participation in a National Health Service in England. - Bifarin, Oladayo; Miah, Jahanara; Harvey, Michelle; Faragher, Gail; Thai, Jade; Dewar, Dennis; Garden, Jenny; Nicholson, Lindsey; Wilson, Nicola; Husain, Nusrat; Joyce, Dan W. (Health Expectations, 2025)
Background: Research‐active National Health Service (NHS) services are linked to better care quality and health outcomes. However, traditional research participant recruitment methods, such as 'opt‐in' strategies, often face challenges in reaching diverse populations. The 'Count Me In' (CMI) system was introduced to address these barriers through an 'opt‐out' model, aiming to normalise research participation and promote inclusivity. At Mersey Care NHS Foundation Trust, a bottom‐up approach was employed to adapt CMI, ensuring meaningful engagement with service users, carers and communities in its design and implementation. Methods: CMI was co‐produced with stakeholders through a series of workshops, discussion groups and consultations with over 300 participants, including service users, carers and NHS staff. Key activities included listening exercises to understand concerns, co‐designing campaign materials and forming a Patient and Public Involvement and Engagement (PPIE) Advisory Group. The group provided ongoing guidance to ensure that the system aligned with the needs of underserved communities and upheld ethical and cultural sensitivity. Findings: Stakeholders widely supported the 'opt‐out' approach, recognising its potential to improve research inclusivity. Participants highlighted the importance of clear communication, cultural sensitivity and robust data protection measures. Specific research priorities, such as mental health and social isolation, were identified. Co‐produced materials, including plain‐language guides and culturally appropriate visuals, addressed concerns about privacy, stigma and accessibility, fostering trust and confidence in the system. Conclusion: The CMI system is an acceptable and scalable model for inclusive research recruitment, embedding research into routine care. The bottom‐up approach ensured the system was tailored to local needs, promoting equity and accessibility. Patient and Public Contribution: A partnership approach working with PPIE leads at the Mental Health Research for Innovation Centre (M‐RIC) ensured that service users, carers and community members shaped the CMI system through extensive co‐production activities. The development of the system, therefore, reflected their lived experiences and priorities, thereby enhancing its inclusivity and impact.